Neurophysiological prognosis in comatose patients after cardiac arrest: The Italian Multicentric Study (ProNeCA). Issue 1 (January 2019) - Carrai, R.; Grippo, A.; Lombardi, M.; Minardi, C.; Vitelli, E.; Politini, L.; Minicucci, F.; Mecarelli, O.; Valzania, F.; Sabatini, R.; Marelli, A.; Celani, M.G.; et al.
Abstract : SEPs are reliable predictor of poor outcome in comatose patients after cardiac arrest (CA). Recently also the role of EEG has been reassessed. To evaluate the prognostic value of EEG and SEPs association in post-anoxic coma at different recording time. We included comatose patients after CA. EEG and SEPs were recorded within 12 hs and at 72 hs after CA. EEG was classified into grade 1("continuous"/"nearly-continuous") and grade 2(discontinuous/burst-suppression/suppression/isoelectric). SEPs were dichotomized into "bilaterally absent" (BA) and "present". Outcome was evaluated at 6 months by GOS. "Recovery of consciousness" was considered good outcome. Ten centers took part to the study and 282 patients were included. EEG and SEPs were recorded in 141 within 12 hs in 162 at 72 hs. Grade 1 EEG at 12 hs always predicted good outcome, grade 2 pattern at 72 hs predicted poor outcome with higher predictive power. BA SEPs always predicted poor outcome. Grade 1 EEG was always associated with present SEPs. EEG is a reliable time-dependent predictor of good outcome (within 12 h) and poor outcome (after 72 h). SEP is time-independent predictor of poor outcome. Early grade 1 EEG is never associated with BA SEP. Early association recordings of EEG and SEPs increase of the reliability of prognosis prediction in post-anoxic coma.